Monocyte-to-high-density lipoprotein cholesterol ratio: A candidate parameter for a risk assessment model in COVID-19 - Argun, Derya; Argun, Ferit; Basım, Pelin; Bayraktaroğlu, Mesut (Verlag Klinisches Labor GmbH, 2022)
Background: COVID-19 has become a pandemic and threatened human public health across the world. Determining effective predictive biomarkers that can classify patients according to risk levels is critical to identify cases that can potentially progress to severe complications and death with the rapid progression of the disease. Therefore, we aimed to investigate the utility of the monocyte-to-high-density lipoprotein cholesterol ratio (MHR), a recently emerging inflammatory marker, as a clinically useful inflammation-based marker in determining patients at higher risk of decreased overall survival in patients with COVID-19. Methods: The demographics, laboratory data, and MHR of 127 patients with laboratory confirmed COVID-19 were evaluated in terms of clinical outcomes. The patients discharged from the hospital constituted the survivor group, while those that died were evaluated as the non-survivor group. Results: The MHR values were found to be significantly higher in the non-survivor group compared to the survivors (p < 0.05). The high-density lipoprotein cholesterol (HDL-C) values were significantly lower in the non -survivor group (p < 0.05), while there was no statistically significant difference in the monocyte values (p > 0.05). Spearman's analyses revealed no correlation between the MHR values and white blood cell, neutrophil, ferritin, D-dimer, and C-reactive protein (CRP) in the non-survivor group (p > 0.05). According to the binary logistic regression analysis model, the neutrophil, ferritin, D-dimer, CRP, and MHR values the most significant factors in predicting survival (p = 0.021, p = 0.004, p = 0.000, p = 0.001, and p = 0.016, respectively), and an increase in the neutrophil, ferritin, D-dimer, CRP and MHR values decreased the survival rate by 1.1, 1.5, 1.8, 1.6, and 1.7 times, respectively. Conclusions: MHR can help predict the severity of the COVID-19 disease and patient outcomes. Therefore, this parameter can serve as a clinically useful and potentially predictive inflammation-based marker for identifying patients with COVID-19 who are at higher risk of decreased overall survival. Considering the serious consequences of the current and possible future pandemics, the establishment of a risk assessment model, including MHR in COVID-19 and similar infections is of vital importance in reducing morbidity and mortality by identifying potential risk factors that can predict the course of the disease. (Clin. Lab. 2022;68:xx-xx. DOI: 10.7754/Clin.Lab.2022.210755)
Keywords: COVID-19; Inflammation; Monocyte-to-High-Density Lipoprotein Cholesterol Ratio